2-Phenyl-8-(1-phenylallyl)-chromenone compounds have a pan-PPAR modulator pharmacophore. Issue 13 (1st July 2019) - Ahn, Sungjin; Kim, Jungmin; An, Seungchan; Pyo, Jeong Joo; Jung, Daram; Lee, Joochang; Hwang, Seok Young; Gong, Junpyo; Shin, Iljin; Kim, Hong Pyo; Kim, Hyoungsu; Noh, Minsoo
Graphical abstract: Highlights: 2-Phenyl-8-(1-phenylallyl)-chromenones promotes adiponectin secretion. 2-Phenyl-8-(1-phenylallyl)-chromenones are pan-PPAR modulators. Pan-PPAR regulating chromenones have therapeutic potential in metabolic diseases. Abstract: Adiponectin is an adipocytokine with insulin-sensitizing, anti-atherogenic, and anti-inflammatory properties. Adiponectin secretion-inducing compounds have therapeutic potential in a variety of metabolic diseases. Phenotypic screening led to the discovery that 5, 7-dihydroxy-8-(1-(4-hydroxy-3-methoxyphenyl)allyl)-2-phenyl-4 H -chromen-4-one (compound1 ) had adiponectin secretion-inducing activity during adipogenesis in human bone marrow mesenchymal stem cells (hBM-MSCs). Compound1 was originally reported to be an anti-cancer chemical isolated from natural honeybee propolis, and its adiponectin secretion-inducing activity was found in non-cytotoxic concentrations. In a target identification study, compound1 and its potent synthetic derivative compound5 were shown to be novel pan-peroxisome proliferator-activator receptor (PPAR) modulators. Molecular docking models with PPARs have indicated that the binding modes of chromenone compounds preferentially interacted with the hydrophobic ligand binding pocket of PPARs. In addition, chromenone compounds have been shown to result in different phenotypic outcomes in the transcriptional regulation of lipid metabolic enzymes than those of selective PPAR mono-agonists for PPARα, PPARγ, and PPARδ. In line with the pharmacology of adiponectin and PPAR pan-modulators, compounds1 and5 may have diverse therapeutic potentials to treat cancer and metabolic diseases.